2018
DOI: 10.1007/s11906-018-0800-3
|View full text |Cite
|
Sign up to set email alerts
|

Possible Breathing Influences on the Control of Arterial Pressure After Sino-aortic Denervation in Rats

Abstract: Recent studies show that baroreceptor afferent stimulation or removal (SAD) results in changes in the respiratory pattern. Changes in the neural respiratory network and in the respiratory pattern must be considered among mechanisms involved in the modulation of the MAP after SAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 90 publications
1
8
0
2
Order By: Relevance
“…Our previous studies showed that rats express significant changes in the respiratory pattern 3 days after SAD (Amorim et al., ). Although the respiratory changes in SAD rats are interesting, an important issue that has not been addressed before is the neural mechanisms causing these adjustments in the breathing pattern after the removal of baroreceptor afferents (Amorim et al., ; Amorim, Souza, & Machado, ). Our working hypothesis was that the longer inspiration observed in SAD rats was associated with changes in the firing properties of the respiratory neurons of the central pattern generator within the brainstem.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous studies showed that rats express significant changes in the respiratory pattern 3 days after SAD (Amorim et al., ). Although the respiratory changes in SAD rats are interesting, an important issue that has not been addressed before is the neural mechanisms causing these adjustments in the breathing pattern after the removal of baroreceptor afferents (Amorim et al., ; Amorim, Souza, & Machado, ). Our working hypothesis was that the longer inspiration observed in SAD rats was associated with changes in the firing properties of the respiratory neurons of the central pattern generator within the brainstem.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the neural respiratory pattern after SAD (marked by longer inspiration) might contribute to the modulation of the sympathetic outflow, with an impact on vascular resistance and, consequently, on arterial blood pressure (Amorim et al., , ). Previous studies from our laboratory documented that at least three subpopulations of presympathetic neurons displayed respiratory‐related activity, including neurons that are inhibited during inspiration (Moraes et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations